Revolutionizing Electric Utilities: The Transformative Potential of Blockchain Technology - Rajesh Kolli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative potential of blockchain technology in the electric utility industry, a sector valued at $2.4 trillion globally. It examines how blockchain addresses critical challenges in grid management, renewable energy integration, customer engagement, and security. The study highlights blockchain's ability to enhance operational efficiency, facilitate peer-to-peer energy trading, improve customer satisfaction, and reduce fraud. Key benefits include potential grid efficiency improvements of up to 30%, increased local renewable energy consumption by 35-40%, and significant reductions in billing errors and customer complaints. Despite challenges such as high infrastructure costs, regulatory hurdles, and scalability concerns, the blockchain in energy market is projected to reach $34.7 billion by 2029, with experts predicting it will play a crucial role in shaping the future of utilities. The article provides a comprehensive overview of blockchain's applications, benefits, and challenges in the utility sector, supported by industry data and expert predictions.
Keywords: Blockchain; Electric Utilities; Renewable Energy Integration; Grid Management; Energy Security